Ideologi Di Balik Mitos Dalam Cerpen Akagaeru Karya Shimaki Kensaku: Kajian Semiologi Roland Barthes - Sulatri, Ni Luh Putu Ari; Damayanti, Silvia (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 1 (2022)DO - 10.24843/JS.2022.v04.i01.p08, 2022)
This article examines the ideology of Shimaki Kensaku in the short story Akagaeru. This study is qualitative research by applying the hermeneutic method. This study uses the semiology theory of Roland Barthes with a two-level sign interpretation model. The results of the study show that at the language level, the signifier of akagaeru refers to the signified of reddish-brown type of frog endemic to Japan. The signified at the language level become the signifier of connotation at the myth level which refers to the signified of connotation namely 1) return to the original Japanese ideology; 2) the failure of communist ideology to develop in Japan; 3) acceptance of the destruction of communist ideology in Japan; and 4) persistence of admiration for communist ideology. These signified of connotations form a myth that is connected with Shimaki Kensaku's ideology, namely suichoku tenk? 'vertical tenk?'